Development of a Chirp Stimulus PC-Based Auditory Brainstem Response Audiometer - Ali Al-Afsaa; Soegijardjo Soegijoko (Journal of Engineering and Technological Sciences, 2004)
Hearing losses during infancy and childhood have many negative future effects and impacts on the child life and productivity. The earlier detection of hearing losses, the earlier medical intervention and then the greater benefit of remediation will be. During this research a PC-based audiometer is designed and, currently, the audiometer prototype is in its final development steps. It is based on the auditory brainstem response (ABR) method. Chirp stimuli instead of traditional click stimuli will be used to invoke the ABR signal. The stimulus is designed to synchronize the hair cells movement when it spreads out over the cochlea. In addition to the available hardware utilization (PC and PCI board), the efforts confined to design and implement a hardware prototype and to develop a software package that enables the system to behave as ABR audiometer. By using such a method and chirp stimulus, it is expected to be able to detect hearing impairment (sensorineural) in the first few days of the life and conduct hearing test at low frequency of stimulus. Currently, the intended chirp stimulus has been successfully generated and the implemented module is able to amplify a signal (on the order of ABR signal) to a recordable level. Moreover, a NI-DAQ data acquisition board has been chosen to implement the PC-prototype interface.